2020
DOI: 10.3389/fcell.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Zebrafish Rab28 Causes Defective Outer Segment Shedding, but Not Retinal Degeneration

Abstract: The photoreceptor outer segment is the canonical example of a modified and highly specialized cilium, with an expanded membrane surface area in the form of disks or lamellae for efficient light detection. Many ciliary proteins are essential for normal photoreceptor function and cilium dysfunction often results in retinal degeneration leading to impaired vision. Herein, we investigate the function and localization of the ciliary G-protein RAB28 in zebrafish cone photoreceptors. CRISPR-Cas9 generated rab28 mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 63 publications
(81 reference statements)
4
26
0
Order By: Relevance
“…In summary, our results suggested that the concerted effect of the structural perturbation induced by the T26N variant on the proximal switch 1 region (Figure 8) and on the distant β5-β6 region would affect both GTP-GDP exchange and Mg 2+ -binding, thus classifying the substitution as a partial loss-of-function missense mutation. Overall, our findings are perfectly in line with several previous lines of evidence on Rab family proteins [17], as the T26N mutation affects the last residue of the broadly conserved G motif among GTPases, and it is widely used to mimic a "GDP-locked" state of Rab proteins [10,13,16,17] due to the disruption of Mg 2+ binding site and the resultant 100-fold decrease in affinity for GTP. Concerning the nonsense p.(Arg137*) variant, no nonsense-mediated decay of mRNA was previously reported [2] on CORD patients carrying such variant, suggesting potential functional defects as the pathological mechanism.…”
Section: Molecular Modeling and Molecular Dynamics Simulations Analyssupporting
confidence: 91%
See 4 more Smart Citations
“…In summary, our results suggested that the concerted effect of the structural perturbation induced by the T26N variant on the proximal switch 1 region (Figure 8) and on the distant β5-β6 region would affect both GTP-GDP exchange and Mg 2+ -binding, thus classifying the substitution as a partial loss-of-function missense mutation. Overall, our findings are perfectly in line with several previous lines of evidence on Rab family proteins [17], as the T26N mutation affects the last residue of the broadly conserved G motif among GTPases, and it is widely used to mimic a "GDP-locked" state of Rab proteins [10,13,16,17] due to the disruption of Mg 2+ binding site and the resultant 100-fold decrease in affinity for GTP. Concerning the nonsense p.(Arg137*) variant, no nonsense-mediated decay of mRNA was previously reported [2] on CORD patients carrying such variant, suggesting potential functional defects as the pathological mechanism.…”
Section: Molecular Modeling and Molecular Dynamics Simulations Analyssupporting
confidence: 91%
“…Recent studies on RAB28 knockout mice showed that Rab-28 plays an essential role in cone-specific disc shedding and phagocytosis and an impaired membrane shedding at the distal COS and/or failed phagocytosis by the RPE has been proposed as possible pathogenetic mechanism for CORD [9]. The role of Rab-28 in regulating membrane shedding from cone outer segment tips has been confirmed in a RAB28 knockout zebrafish model where, however, a longer visual function with no sign of retinal degeneration up to 12 months has been observed [10]. In humans, only six RAB28 variants have been reported to be associated with CORD.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations